Analisis Parenting Education terhadap Peningkatan Pembinaan Anak Usia Dini di Taman Kanak-Kanak (TK) Al Huda Kecamatan Hinai - Wiguna, Satria; Nurmisdaramayani, Nurmisdaramayani (STAI Denpasar Bali, 2024)
Parenting education is usually provided by formal and non-formal educational institutions with different target focuses, types and methods of delivering parenting education. The sample in this study was the parents, guardians of students from TK/KB Al-Huda Batu Melnggang, Hinai District, totaling 60 respondents. The data collection techniques used in this research were questionnaires, observation and documentation. For data analysis techniques using a simple linear regression method was used to analyze the data assisted by the SPSS 26 program. The results of the research were that based on hypothesis testing from the calculated t value of the perceived usefulness variable (X1) of 9,023 < 1,670 with a significance value of 0.000. Because the calculated t value is greater than the t table and the significance value is smaller than the required 0.05, it can be concluded that the Parenting Education variable has a significant effect on the satisfaction variable for Increasing Early Childhood Development in Kindergarten. So, it can be concluded that the Parenting Education variable has an influence on increasing early childhood development in kindergarten.